(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
Health is the main capital of the nation’s progress because every citizen of Indonesia is entitled to health services. Health problems for residents in the city as well as in rural Indonesia are still a problem that still exists to this day. It can be seen from the number of health programs that are implemented and continue to be developed has not run well, whether it is a new health program or health program results modification of the old program. One program that has not reached the target as expected is delivery help. Almost throughout Indonesia there are still many deliveries assisted by the village cultivators. II. The purpose of this research is to know the role of the village custodian to help pregnant mother give birth in Bailang Village, Bunaken Sub-district, Manado City. The method used by researchers is qualitative research. Researchers want to know the attitude of the community, family, pregnant women, especially the village culprit help mothers give birth. As for this research take informant which is focus of this research is 5 months pregnant mother 1 person, pregnant mother 7 month 1 person, pregnant mother 8 month 1 person, mother giving birth by one of the villager cultivator, village culprit Train , Midwife 1 person (as pengelolah program), family companion 1 person, Key informant who domiciled in Kelurahan Bailang District Bunaken 1 person. The research has been conducted for 2 months, starting from June to July 2017 in Bailang Village, Bunaken Sub-district, Manado City. Delivery aid by a non-medical health worker is performed by a person who is called a village culprit, a prelim village culprit is a person who is considered skilled and trusted by the community to help mother and child deliveries and care according to the needs of the community. The community’s belief in the skill of the village master is related to the cultural values of the local community. Usually the village culprit helps the delivery without regard to safety, hygiene and mechanisms as it should be so that various complications can result in death. Basically a village culprit, based on the belief of the local community or is a work that has been passed down from generation to ancestor or family and usually have aged Â± 40 years and over. This research would like to highlight the social life of coastal communities learned from the existence of coastal communities in which it contains elements of the institutions. The theory used in this research is role theory. The results obtained cultural traditions of pregnant women based on hereditary cultures from parents to the generation of pregnant women have been accustomed and also the belief to the village cultivator in taking the choice because pregnant women feel more confident to the village culprit in assisting labor using ritual (customs) in terms of sevenmonthly prayer reads of pregnancy. The village cultivator can not assess the risks of very young pregnant women and the age of high risk pregnant women. The village cultivator in helping delivery has knowledge in terms of experience not based on education, because education is only a village cultivation graduates SR (Sekolah Rakyat / SD-level) and some are literate.